Factors affecting academic performance among form six students in Kolej Tingkatan Enam Desa Mahkota, Kuala Lumpur - Cecilia, Lurthusamy (2018)
Academic performance is the extent to which a student, teacher or institution has achieved their short or long-term educational goals and strongly linked to the positive outcome values. Based on this academic performance a research was conducted at Kolej Tingkatan Enam Desa Mahkota, Kuala Lumpur. Further, this research intended to investigate how teaching methods, motivation and time management will influence academic performance among Form Six students. This research was based on the Adult Learning Theory by Knowles (1984). A simple random sampling procedure was used to select 161 students from the total of 276 students. The data was collected by using questionnaires and was analysed by using the SPSS version 20. Additionally, multiple linear regression were used to identify relationship between the variables. The research results indicated that there is a relationship between time management and academic performance. In concluding this research, the management suggestions as well as suggestion for future research was discussed. A more detailed study with bigger sample involving more school is suggested to get a clearer picture of the factors that affecting academic performances among Form Six students.